A study on the oil transport in piston skirt-cylinder liner under fully flooded conditions using improved SPH simulations. (December 2019) - Li, Haiqiao; Liu, Hantao; Jiang, Shan; Chang, Jianzhong
Abstract: In the present work, we studied the mechanical friction losses of the piston assembly-cylinder system that can be reduced by the fully flooded hydrodynamics lubrication during the oil film developed between the piston skirt and the cylinder liner. The lubricating oil transport process was described with Navier-Stokes equations in the clearance of piston skirt and liner with the piston reciprocating motion based on fully flooded hydrodynamics lubrication. The improved SPH method was then used to study such oil transport process with the piston reciprocating motion for the first time. The effects of the viscosity of lubricating oil, inertia force of oil film, the velocity of piston reciprocating motion, oil film thickness on oil transport were studied systematically. It was found that the inertia force of oil film plays a very important role in oil transport process under the condition of large clearances between the piston skirt and cylinder liner, small kinematic viscosities (i.e. large Reynolds numbers), and/or large frequencies of velocity evolution (i.e. large velocity gradient of piston reciprocating motion). Specifically, the results demonstrate that the internal friction effect of the fluid becomes prominent on maintaining the stability of lubricating oil transport process. It is also found that influence of the velocity of piston reciprocating motion on oil flow stable is not obvious. We expect that the study presented here can provide a useful guidance for the design of low-mechanical friction losses internal combustion engines.